TANGGUNG JAWAB PELAKU USAHA TERHADAP KONSUMEN MAKANAN INSTAN KADALUWARSA DI PASAR TRADISIONAL KOTA SAMARINDA - Lady Chintya Ramadhani (Universitas 17 Agustus 1945 Samarinda, 2020)
ABSTRACTMany business people are competing to issue instant food products in the community because instant food is one of the fast and simple food products that can be practically consumed by the public. This makes business people forget to present the best quality to consumers. Business actors only fulfill the number of goods produced not with good quality.This study is empirical normative law research that is a form of research based on or sourced from literature such as books, documents, legislation, and scientific works related to the title and main problems in this writing. The research procedures used are Library Studies, Field Studies, and Data Processing. Then analyzed qualitatively. From the results of the research that has been conducted and analyzed, the Acting Responsibilities of Business Expenditures for Instant Food Products Circulating in the Traditional Market of Samarinda City Based on Act Number 8 of 1999 concerning Consumer Protection, namely business actors are obliged / responsible to guarantee the quality of goods produced / traded (providing information clear / correct conditions and guarantees of goods), Rights of Expired Instant Food Consumers Circulating in Traditional Markets in a Safeguard to compensate for losses not only caused by unlawful acts, but may be caused by negligence or negligence and carried out by himself or people who are under his supervision, and Law Enforcement and the Role and Responsibility of the Food and Drug Supervisory Agency (BPOM) on Expired Instant Food Products in Kota Samarinda Food Drug Monitoring System (SisP OM) which is effective and efficient that is able to detect, prevent and supervise Products including to protect the safety, safety and health of consumers. Keywords: Products, Food and Expiration